PENGARUH GAYA KEPEMIMPINAN DAN KEDISIPLINAN TERHADAP KINERJA PADA PEGAWAI KANTOR CAMAT SAGULUNG - Lidia Saputri; Ade Parlaungan Nasution; Ramon Zamora (EQUILIBIRIA, 2017)
The research was conducted in the District Sagulung. The purpose of this study was to determine the effect of leadership style and discipline to the performance, both separately (partial) and collectively - together (simultaneously).          In this study, the authors use the method of sample with a total of 35 people to serve as respondents of the total population (employees). While the types of data used are primary data and secondary data. Sources of primary data obtained from questionnaires to employees in the district kompoten Sagulung While the secondary data obtained from the District Office Sagulung and documents obtained from the literature - literature-related and can support as well as useful for this research. Data was collected through interviews and questionnaires. Data were analyzed by descriptive statistics, which are used to describe the objects that give an overview of the study through the data with methods drawn from a population sample obtained in the field associated with the theory - a theory that is relevant and quantitative techniques to the analysis of the data that has been given a score according to the measurement scale used is the Likert scale and the results of the test using SPSS (Statistical Product and Service Solutions) version 20.         From the research, the authors conclude that the partial leadership style (X1) and a significant positive effect on performance (Y), with test results for 0919 or 91.9%, and Discipline (X2) is also a significant effect on performance (Y), it can be seen from the test results for 0884 or 88.4%. Then the simultaneous testing Leadership Style and Disciplinary positive and significant effect (strong) on Employee Performance in Batam City District Sagulung to sled for 0834 or 83.4%, as for the rest of 0166 or 16.6% influenced by variables or other factors.